Landscape Diversity: Multiple-Use Landscapes for Reclaimed Phosphatic Clay Areas - Edward A. Hanlon; Matt Wilson; Casey Beavers; James Cates (EDIS)
With planning, communities can use reclaimed phosphatic clay areas for agriculture and at the same time restore lost wetlands, improve water quality and water use efficiency, and retain areas valuable to wildlife. This revised 5-page concept paper was written by E.A. Hanlon, M. Wilson, C. Beavers, and J. Cates, and published by the UF Department of Soil and Water Science, August 2011.